A Historical Overview of the Process of Inclusion of People with Disabilities in the Labor Market (Research, Society and Development, 2020)
The paper presented deals with a current theme, which is the person with disabilities in the labor market, given that the relationship with work is at the heart of the problem of exclusion, and that according to government data, there are a significant number of people with disabilities. disabilities who are excluded from the work process, that is, their formation of the deficient subject. Reserving vacancies in the job market for People with Disabilities is law and represents a victory in the conquest of rights. However, the process of hiring people with disabilities is often a matter of mere integration, which does not guarantee their development as a citizen. This documentary research analyzed the historical path of people with disabilities about their insertion in the labor market throughout history. The research will be developed in four phases, in which we will use the following instruments: document analysis, observation (free and directed), semi-structured interview and objective questionnaire. The content analysis technique will guide the organization and discussion of the material collected in the first and second phase of the study. In this article we will present the data from the first phase. The study offers possibilities for reflection on the process of insertion of people with disabilities in organizations.